Dengueside Survival: Providing a serious board game to fight against the Aedes aegypti mosquito - Azevedo, Gabriel Silva de (2022)
The Aedes aegypti mosquito is the vector for transmitting diseases that represent a recurring public health problem. Different educational campaigns and activities have been developed for mosquito prevention and control, such as the production of educational games. This paper presents the final result of the conception, design, construction and validation of the “Dengueside Survival”, a serious board game that presents the fight against the Aedes aegypti mosquito in a cooperative perspective. Dengueside provides five initial missions for players who must act as health agents to complete the proposed combat and control missions against the mosquito. For the validation of the proposed game, matches in physical and virtual environments were carried out, together with the application of the MEEGA+ questionnaire on the respective players, showing as a result the viability of the proposed game as a playful tool to support awareness of the fight against mosquitoes.